Aspectual composition in "ser/estar + adjective" structures: adjectival scalarity and verbal aspect in copular constructions - Gumiel, Silvia; Pérez-Jiménez, Isabel (Borealis – An International Journal of Hispanic Linguistics, 2012)
The distribution of the Spanish copulas ser and estar (‘be’) (specifically in the syntactic context <ser/estar + A>) has been generally accounted for in the literature in aspectual terms, more explicitly, in terms of the distinction between individual-level and stage-level predicates. Our claim is that the distributional properties of adjectives in the <ser/estar + A> structure can be better described if the scalar properties of the adjectives are taken into account, crucially those properties related to the relative vs. absolute distinction (in the sense of Kennedy & McNally 2005): relative adjectives combine with ser, absolute adjectives combine with estar. From this hypothesis, a better theory arises about aspectual composition in the domain of stative predications (in the line of Husband 2010, 2012).